Designing SOP for physical work environment maintenance based on ISO 14001: 2015 and Permenaker No.5 of 2018 at PT XYZ - Murfid, Nurjihan Aqilah; Widaningrum, Sri; Safrudin, Yunita Nugrahaini (Universitas Mercu Buana, 2025)
The work environment in a company is a working condition to provide a comfortable working atmosphere and situation for employees in achieving the goals desired by a company. PT XYZ is a manufacturing company that focuses on the production of socks. Based on interviews with workers in the production area, workers complained about problems related to the physical work environment. Therefore, researchers conducted sampling on the lighting factor and noise factor, and there were several work areas that did not meet the predetermined standards and criteria. So, this research aims to design a Physical Work Environment Maintenance SOP that has been adjusted to ISO 14001:2015 Clause 9.1.1 concerning Environmental Management Systems and Permenaker No. 5 of 2018. This SOP design uses the Business Process Management (BPM) method. This research produces a Physical Work Environment Maintenance SOP, which includes physical work environment maintenance procedures and supporting documents consisting of physical work environment maintenance plan forms, checklist forms, list budgeting forms, findings and corrective action forms, and final reports. The results of the SOP design in this design are expected to assist in providing structured and detailed guidance covering the identification of nonconformities, the repair process, and the evaluation of corrective actions.